PENGARUH PEMBELAJARAN DARING TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN EKONOMI KELAS XII IPS SMA NEGERI 1 KOTA JAMBI - Das Alecta M, Tiara Ananda; Afrila, Diliza (Universitas Batanghari Jambi, 2022)
This study aims to determine the effect of online learning on student learning outcomes in the economics subject of Class XII Social Studies at SMA Negeri 1 Jambi City. This research design uses quantitative research methods with data collection techniques through observation and questionnaires. Where the population in this study were 139 students with a research sample of 103 students. The data management techniques in this study are the validity test of the research instrument, the research reliability test, quantitative descriptive analysis, normality test, homogeneity test and simple regression test. The results showed that (1) online learning at SMA Negeri 1 Jambi City in economic subjects obtained a TCR of 67.674% which was categorized as quite good. Of the 103 students in class XII IPS, there were 34 students who scored above the KKM, and 17 students scored the same as the KKM, while 52 other students scored below the KKM. Based on the results of hypothesis testing, it is known that there is an effect of online learning on learning outcomes in economics class XII social studies at SMA Negeri 1 Jambi City. This can be seen from the t count is greater than the t table (2.188 > 1.9834) at a significant level of 0.05. So Ha is accepted and Ho is rejected, meaning that there is an effect of online learning on the variables of student learning outcomes in economics class XII Social Sciences SMA Negeri 1 Jambi City. Based on the Summary model coefficient table, it is known that the influence of online learning variables on student learning outcomes is 21.3%. In the R Square table of 4.5% which shows the influence of other variables that affect student learning outcomes.Keywords: Online Learning, Learning Outcomes